Development of a Family Meal Plan Application with Voice Recognition, Siri Integration, and Nutrition Management Using Data-Driven Approach - Livanty Efatania Dendy; Celinka Eira Jove; Rinabi Tanamal (SISFORMA, 2026)
Maintaining a healthy diet has become increasingly important as fast-food consumption rises and nutritional balance is often overlooked. This research proposes a technology-based Family Meal Plan Application equipped with voice recognition, Siri integration, nutrition management, and automated grocery lists to assist home cooks in planning healthier meals more efficiently. The application was designed using Figma, developed with Flutter, and integrated with the Siri API to provide a seamless hands-free experience during cooking. A nutrition prediction model was also developed using a Kaggle dataset and deployed locally to generate real-time nutritional analysis. The final results of this study show that the application prototype successfully meets user needs in simplifying weekly meal planning, providing accurate voice-based cooking guidance, and offering automated nutrition calculations for each family member. User testing involving home cooks indicated increased efficiency in meal preparation, reduced cognitive load during recipe execution, and improved awareness of daily nutritional intake. The voice command system operated with high accuracy and responsiveness, while the automated grocery list feature significantly streamlined weekly shopping activities. Overall, the application demonstrates strong potential to support healthier family eating habits through an intelligent, data-driven, and user-friendly solution.